Prevalence of severe ADHD: an epidemiological study in the Italian regions of Tuscany and Latium. (15th September 2014) - Donfrancesco, R.; Marano, A.; Calderoni, D.; Mugnaini, D.; Thomas, F.; Di Trani, M.; Innocenzi, M.; Vitiello, B.
Abstract : Background: The rate with which attention deficit/hyperactivity disorder (ADHD) is diagnosed varies widely across countries, suggesting that cultural factors influence the clinical interpretation of child behaviour. This study estimated the point prevalence of severe ADHD among elementary and middle-school Italian children. Method: An epidemiological sample of 2016 children attending 2nd–8th grade in the Italian regions of Tuscany and Latium was selected based on census distribution of the school-age population. Teachers completed the Italian version of the ADHD Rating Scale for Teachers (SDAI). For children with at least six inattention symptoms and/or at least six hyperactivity/impulsivity symptoms rated 'very often' by the teachers, the parents completed the Italian ADHD Rating Scale for Parents (SDAG). Children with documented ADHD symptoms at both school and home received a complete psychiatric interview with the Kiddie Schedule for Affective Disorders and Schizophrenia-present and lifetime version (K-SADS-PL). Results: Of the 1887 assessed children, 4.45% (95% CI 3.58–5.51) met the ADHD cut-off on teacher ratings, 1.43% (0.96–2.12) had ADHD symptoms endorsed by both teacher and parent, and 1.32% (0.87–1.97) were further confirmed by the psychiatric evaluation. The male:female ratio was 7:1. The inattentive type accounted for about half of the ADHD cases. Conclusions: When applying stringent criteria for both severity and pervasiveness of symptoms, it is estimated that about 1.3% of the Italian elementary and middle-school children suffer from severe ADHD.